Research and Implementation of Synthesis Modulefor Parlay X in Monitoring System Platform of Value-Added Service - Peng Luo; Jiangtao Luo; Chengchao Xiang; Zunyi Chen (Dianxin kexue)
Integrated access gateway northbound interface of Parlay X 2.0 interfaces were described in detail. The signaling procedures in Parlay X interfaces of value-added business platform were deeply analyzed and studied. It also took the MMS business processes as an example, which conducted CDR synthesis scheme in the Parlay interfaces service classification and process analysis with Hash indexing algorithm. The algorithm was tested and validated with capturing network data, which obtained good results.